233k views
3 votes
Subtract the expressions: (5z + 4) - 5(-3z -6)

User Odile
by
5.8k points

2 Answers

5 votes

Answer:

20z + 34

Explanation:

User Mattwallace
by
5.3k points
6 votes

Hey there!

“(5z – 4) – 5(–3z – 6)”

DISTRIBUTE the RIGHT side of your equation

5z – 4 –5(–3z) + (–5)(–6)

–5(–3) = 15z

(–5)(–6) = 30

NEW EQUATION: 5z – 4 + 15z + 30

COMBINE your LIKE TERMS

(5z + 15z) + (4 + 30)

5z + 15z = 20z

4 + 30 = 34

ANSWER: 20z + 34 ☑️

Good luck on your assignment and enjoy your day!

~LoveYourselfFirst:)

User DGS
by
5.1k points